Effect of Resin Luting Film Thickness on Fracture Resistance of a Ceramic Cemented to Dentin - Anuradha Prakki, DDS, MS;1 Renato Cilli, DDS, MS;1 Alcides U. Da Costa, (Journal of Prosthodontics, 2007)
The aim of this study was to evaluate the fracture resistance of ceramic plates cemented to dentin as a function of the resin cement film thickness